Preparation Pilocarpine Hydrochloride Selective Electrodes - Abass, Amina M (Al-Nahrain Journal of Science, 2017)
New eight selective electrodes of pilocarpine hydrochloride deepened on complexes of (PCH) -molybdophosphoric acid and (PCH) – phosphotungstate were prepared with varied plasticizers. Electrode with complex (DBPH-MP) was used as an active material, gave linear range from 5.0×10-2 to 6.0×10-5 M, and slope was 62.01 mV/decade, with detection limit was 2.0×10-5M, lifetime was near to 60 days. Electrode,s membrane made with active material (DBP-MP), showed concentration range was 2.1×10-3-6.3×10-5M, the slope was near to 52.34 mV/decade. Detection limit was 1.0×10-5M, 55 days was the life time of this electrode. The parameters of electrode deepened on (DBPH-PT), concentration range was from 5.0×10-2 to 6.5×10-5 M with slope 50.41 mV/decade, 2.2×10-5 M was the detection limit.Life time was determined around to 52 days.